Antifungal effect of organic acids on Aspergillus flavus and Penicillium nordicum - Guimarães, Ana Cristina Silva Esperança (2017)
SFRH/BD/103245/2014 (FCT), and UMINHO/BPD/51/2015 from project UID/BIO/04469/2013 (FCT/MEC)